Quantitative ultrasound and photoacoustic imaging for the assessment of vascular parameters - Meiburger, Kristen M. (Springer, 2017)
This book describes the development of quantitative techniques for ultrasound and photoacoustic imaging in the assessment of architectural and vascular parameters. It presents morphological vascular research based on the development of quantitative imaging techniques for the use of clinical B-mode ultrasound images, and preclinical architectural vascular investigations on quantitative imaging techniques for ultrasounds and photoacoustics. The book is divided into two main parts, the first of which focuses on the development and validation of quantitative techniques for the assessment of vascular morphological parameters that can be extracted from B-mode ultrasound longitudinal images of the common carotid artery. In turn, the second part highlights quantitative imaging techniques for assessing the architectural parameters of vasculature that can be extracted from 3D volumes, using both contrast-enhanced ultrasound (CEUS) imaging and photoacoustic imaging without the addition of any contrast agent. Sharing and summarizing the outcomes of this important research, the book will be of interest to a broad range of researchers and practitioners in the fields of medical imaging and biomedical engineering.
Keywords: Ultrasonics.; Ultrasonic imaging.; elektronické knihy; electronic books